The FcμR Limits Tonic BCR Signaling by Regulating IgM-BCR Expression - Nguyen, Trang T. T. (Nat Immunol, 2017)
The IgM Fc receptor (FcμR), originally cloned as “Fas-apoptosis inhibitory molecule (FAIM3/TOSO)” can function as a cell surface receptor for secreted IgM on a variety of cell types. We report that FcμR also is expressed in the trans-Golgi network of developing B cells, where it constrains IgM- but not IgD-BCR transport. In FcμR absence, IgM-BCR surface expression was increased, resulting in enhanced tonic BCR signaling. B cell-specific FcμR-deficiency enhanced spontaneous differentiation of B-1 cells, resulting in increases in natural IgM levels, and dysregulated B-2 cell homeostasis, causing spontaneous germinal center formation, increased serum autoantibody titers, and excessive B cell accumulation. Thus, FcμR/FAIM3 is a critical regulator of B cell biology by constraining IgM-BCR transport and cell surface expression.